1964
DOI: 10.1152/ajplegacy.1964.206.5.975
|View full text |Cite
|
Sign up to set email alerts
|

Parachloromercuribenzoate on action potentials of Purkinje and ventricular fibers of hog heart

Abstract: Parachloromercuribenzoate (0.5 to 2.6 x 10–4 m) was administered to a hog Purkinje fiber ventricular muscle preparation and its effects on transmembrane action potentials of the two types of fibers were studied. Parachloromercuribenzoate produced changes in action potential of Purkinje but little change in that of ventricular fiber. The earliest alteration in Purkinje fiber was a decrease in overshoot. This was followed by a decrease in height of action potential and slowing in rate of depolarization. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1964
1964
1978
1978

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is unlikely that parachloromercuribenzoate has any single specific site of action on myocardium metabolism; recent studies of its effect on isolated cardiac tissue (20) suggested and myocardial contractility in hearts deprived of autonomic activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that parachloromercuribenzoate has any single specific site of action on myocardium metabolism; recent studies of its effect on isolated cardiac tissue (20) suggested and myocardial contractility in hearts deprived of autonomic activity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the myocardium, little is known about the effects of sulfhydryl blocking reagents. KLEINFELD et al (1964) reported a decrease in the resting membrane potential and in the overshoot of action potential in hog Purkinje fibers after application of p-chloromercuribenzoic acid (PCMB), and KLEINFELD and STEIN (1968) observed a positive inotropic effect of HgCl2 on the rat atrium. Recently, HALBACH (1975) found that HgCl2 caused a rapidly developing negative inotropic effect followed by a transient increase in the contractile tension of the guinea pig papillary muscle.…”
mentioning
confidence: 99%